Teaching and Learning Styles in Higher Education: Analysis of Student Teachers’ Preferences in an English Pedagogy Program at Three Chilean Universities - Rojas-Jara, Constanza (2016)
This paper shows the findings of a study conducted in three Chilean universities in 2014. It aims to analyze EFL student teachers’ preferences regarding their teaching and learning styles. 279 participants answered the teaching style inventory and 238 took the learning style questionnaire. These participants are first, third and fifth year student-teachers. This study uses Grasha and Riechman’s model to study teaching and learning styles. These authors propose a classification, cluster grouping and integrated clustering (Lewis, 2014; Grasha y Riechmann, 1975). The findings reveal that all student teachers favor the Facilitator teaching style and the Collaborative learning style.